The future of British English in the European Union - Modiano, Marko (English today, 2023)
In the three years and seven months between the referendum on 23 June 2016 and 31 January 2020, when the UK officially left the European Union, there was much speculation over what status English would have in the EU after the withdrawal of the UK. It is now apparent that English has continued to flourish. This is supported by statistics for Member States which chart the extent to which English is a school subject. Well over 95% of the children in the EU are taught English as a mandatory subject. Official EU figures also show that 38% of the population is proficient in English as a second language, three times more than both French and German (Special Eurobarometer 386: Europeans and their Languages, 2012). Moreover, although some, such as Danuta Hübner, EMP, wanted to question whether or not English could maintain its status as an official language in the EU, it is now apparent that it will not be possible to remove English in this respect (with changes requiring a unanimous vote in the Council, which Ireland has said it will not support [European Commission, 2016]), (The Guardian 27 December 2019). English has also retained its position as one of the three ‘procedural’ or ‘working languages’ alongside French and German. This has taken place despite the fact that without the UK, no Member State has English as its official EU language, and only approximately one percent of EU citizens have English as a mother tongue.